High prevalence of colonization of oral cavity by respiratory pathogens in frail older patients with oropharyngeal dysphagia. Issue 12 (28th September 2015) - Ortega, O.; Sakwinska, O.; Combremont, S.; Berger, B.; Sauser, J.; Parra, C.; Zarcero, S.; Nart, J.; Carrión, S.; Clavé, P.
Abstract: Background: Aspiration pneumonia (AP) is caused by dysfunctional swallowing resulting in aspiration of material colonized by respiratory pathogens. The aim of this study was to assess and compare the swallowing physiology, health status, oral health status, and oral/nasal microbiota in frail older patients (FOP) with oropharyngeal dysphagia (OD) and a control group. Methods: We studied 47 FOP (>70 year) with OD by videofluoroscopy (17 with acute pneumonia –APN‐, 15 with prior pneumonia–PNP‐ and 15 without) and 14 older controls without OD (H). Oral/nasal colonization by five respiratory pathogens was evaluated by qPCR, whereas commensal microbiota composition was assessed by pyrosequencing. Key Results: (i) Frail older patients with OD presented similar comorbidities, poor functionality, polymedication, and prevalent videofluoroscopic signs of impaired safety of swallow (33.3–61.5%). However, patients with OD‐APN also presented malnutrition, delayed laryngeal vestibule closure (409.23 ± 115.6 ms; p < 0.05), and silent aspirations (15.6%). (ii) Oral health was poor in all groups, 90% presented periodontitis and 72%, caries. (iii) Total bacterial load was similar in all groups, but higher in the oropharynx (>10 8 CFU/mL) than in the nose (<10 6 CFU/mL) ( p < 0.0001). Colonization by respiratory pathogens was very high: 93% in OD patients ( p < 0.05 vs H); 93% in OD‐PNP ( p < 0.05 vs H); 88% in OD‐APN ( p = 0.07 vs H), and lower in controls (67%). Conclusions & Inferences: Frail older patients with OD had impaired health status, poor oral health, high oral bacterial load, and prevalence of oral colonization by respiratory pathogens and VFS signs of impaired safety of swallow, and were therefore at risk for contracting AP. Abstract : Aspiration pneumonia and oral colonization in patients oropharyngeal dysphagia (OD) are very related. We studied and compared oral colonization by respiratory pathogens in older patietns with OD and a control group. We found higher colonization by respiratory pathogens in the oral cavity of older patients with OD.